Neurocristopathies: How new discnveries in neural crest research changed our understanding - Vega López, Guillermo Alfredo (2018)
Neural Crest Cells (NCC) have long been recognized as the fourth layer of developing vertebrate embryos. Нe neural crest is a transient cell population that is probably heterogeneous but multipotent, giving rise to melanocytes, Schwann cells, sympathetic, parasympathetic and enteric neurons, enteric glia, endocrine cells, fibroblasts, muscle, bone, cartilage and meninges, among others cell types [1]. Нe disorders that stem from neural crest dysfunction, called Neurocristopathies (NCP), are still only partially understood. Despite the great advances in our understanding of NCC formation and development, the causal link leading to NCP has remained elusive. In a recent review dealing with NCP we provided a thorough analysis of 66 NCP associated with a dozen Cell Signaling Pathways, 4 different families of transcription factors and a wide diversity of cellular processes?. In over 5 model organisms (mouse, chicken, frog, fish and others, it has been demonstrated that NCP are linked to NCC faults during essential developmental processes. We also discussed the incorporation of new diseases or syndromes based on the defects of neural crest-derived tissues and organs that have also been unveiled very recently. In the light of recent discoveries, we also included RASopathies, Ciliopathies, Ribosomopathies, and defective epigenetic mechanisms as responsible for four newly established NCP categories.